The Effect of e-SPT Implementation On Increasing Income Tax Revenue for Corporate Taxpayers: Case Study at A Tax Service Office in The City of Bandung - Iwan Sidharta; Maulana Yusup; Siti Mialasmaya (Acman: Accounting and Management Journal, 2022)
This study intends to examine the impact of e-SPT adoption on the growth of business entity taxpayers' income tax revenues. Location of study at one of the city of Bandung's Tax Service Offices. Methods of description and verification are employed for study. The correlation study reveals that the coefficients have a significant link. The findings of the regression analysis indicate that as the e-SPT improves, so do income tax collections. The conclusions of the research imply that the deployment of e-SPT can facilitate the reporting of tax requirements by business taxpayers, hence increasing tax revenue.